KEMAMPUAN PENALARAN MATEMATIS SISWA SMP DALAM MEMECAHKAN MASALAH POLA BILANGAN - Firnanda Pradana Putra; Susiswo Susiswo (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The study was conducted to describe students’ reasoning abilities in solving number pattern problems in class VIII SMP. The research can be categorized as qualitative research. The research subjects selected consisted of 1 high-category student, 1 medium-category student, and 1 low-category student. The research data collection technique was carried out by giving a number of pattern material tests and conducting interviews to research subjects. The results showed that the high-category students had poor mathematical reasoning abilities, the medium-category students had very good mathematical reasoning abilities, and the low categories had poor mathematical reasoning abilities.